PENGARUH BELANJA MODAL DAN FISCAL STRESS TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Padang, Novi Natalia; Padang, Wendi Suprapto (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The aim of this research is to determine and analyze the influence of capital expenditure and fiscal pressure on the financial performance of local governments in districts/cities of North Sumatra Province. The population of this research is districts/cities in North Sumatra Province which consists of 33 districts/cities with observation years from 2014 to 2021. The sample type uses a saturated sample where the population is a sample. The data was processed using the panel data regression statistical test method. The results of this research prove that fiscal pressure has a positive and significant effect on the financial performance of local governments in districts/cities of North Sumatra Province. Meanwhile, capital expenditure has no effect on the financial performance of district/city governments in North Sumatra Province.